2019
DOI: 10.1177/1932296819836987
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Human Factors and Pen Needle Design on Insulin Pen Injection

Abstract: Background: Limited published data exists quantifying the influence of human factors (HF) and pen needle (PN) design on delivery outcomes of pen injection systems. This preclinical in vivo study examines the impact of PN hub design and applied force against the skin during injection on needle penetration depth (NPD). Method: To precisely locate injection depth, PN injections (20 µl; 2 IU, U-100 volume equivalent) of iodinated contrast agent were administered to the flank of Yorkshire swine across a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…3 a as a reference point was the image depicting the most significant application pressure. Proper technique indicates the needle hub should be visible and to avoid indenting the skin when injecting to reduce the risk of intramuscular injection [ 5 , 29 ]. Pen needle hub design, in addition to needle length and injection technique, may help with mitigating excessive user-applied injection force [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 a as a reference point was the image depicting the most significant application pressure. Proper technique indicates the needle hub should be visible and to avoid indenting the skin when injecting to reduce the risk of intramuscular injection [ 5 , 29 ]. Pen needle hub design, in addition to needle length and injection technique, may help with mitigating excessive user-applied injection force [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Structured training and the use of new-generation pen needles can help improve injection technique, leading to significant HbA1c reductions and decreased rates of lipohypertrophy [34,43]. Technological advances in needle design have observed that a 4 mm pen needle injected at a 90°angle results in optimal needle depth penetration, therefore reducing the risk of intramuscular injections [29]. New-generation pen needles have also been associated with more positive patient reviews and improved ease of use [30], and in general, shorter needles are the preferred choice for most patients [25].…”
Section: Role Of New-generation Pen Needle Technology To Support Propmentioning
confidence: 99%
See 1 more Smart Citation
“…One manufacturer (Becton Dickinson) has recently redesigned this hub from a dome to a tip that looks more like a ring. 5 The new hub design aims to reduce the impact of variable injection techniques by dispersing insertion forces across a re-engineered, contoured, and expanded surface area. 5 The design of the hub enables a more comfortable insulin application with a full-length needle penetration regardless of application force.…”
Section: The Force With Which Syringes or Pens Are Inserted Into The Skinmentioning
confidence: 99%
“…For these reasons, a 32 G extra-thin-wall, 5-bevel cannula PN has been re-engineered with a contoured hub with expanded surface area to improve the injection experience and injection depth consistency 21,[25][26][27] . The aim of this investigation, conducted as two separate studies, was to compare user experiences with this redesigned, second generation 32 G Â 4 mm PN (investigational BD 32 G PN: BD Nano i 2nd Gen, also known as BD Nano PRO) versus four thinner and similar length, commercially available PNs (33 G Â 4 mm, 34 G Â 4 mm, and 34 G Â 3.5 mm).…”
Section: Introductionmentioning
confidence: 99%